PENINGKATAN ONSET ESTRUS DAN LAJU OVULASI DOMBA EKOR GEMUK (Ovis aries) MELALUI PENGIMBASAN CAIRAN FOLIKEL SAPI INCREASING ONSET ESTRUS AND OVULATION RATE FAT TAIL EWE (Ovis aries) BY FOLLICULAR FLUID INDUCTION - , Rusdin (Pembangunan Pedesaan, 2006)
The objective of this study was to explore response of the fat tail ewe on increasing prolificacy by bovine follicular fluid (bFF) induction. This study was conducted from March 2003 until May 2004 at the Station of Animal Breeding and Forage, Livestock Services, East Java Province, Garahan-Silo, Jember. The measured responses of bFF induction were onset of estrus and ovulation rate. The study was implemented by using Completely Randomized Design (CRD) with four treatments of follicular fluid volume induction, i.e., bFF0.0 ml, bFF3.5 ml, bFF7.0 ml, and bFF10.5 ml. Each treatment was replicated six times. Results of the study indicated that the bFF induction significantly and highly significantly (P